The Effect of Assertiveness Training Skill on Feelings of Happiness and Mental Health of Students in Iran - Bahram Gheitarani (Journal of Global Pharma Technology, 2017)
Background and objective Assertiveness is one skill that it can change interpersonal relations and cause happiness. Hence, the aim of present study is the effect of assertiveness training skill on feelings of happiness and mental health of students. Methods and materials the method in this study is empirical method with control group. Statistical population in this study consists of all male high school students of Radar City by 2016. Among those students identified with low assertiveness by their teachers and those with low scores in Mental Health Questionnaire, 30 students were selected randomly and were placed in two experimental and control groups. The experimental group received sessions of assertiveness training and control group was remained in waiting list. Both groups fulfilled Happiness Questionnaire and General Health Questionnaire (GHQ) before and after intervention. Data analysis was done using analysis of covariance (MANCOVA) using SPSS-22.Results The results showed that there is significant difference statistically between two groups in terms of amount of happiness and mental health after training assertiveness training (p<0.01). Conclusion Training assertiveness skill can enhance happiness and mental health of students.Keywords: Assertiveness methods, Happiness, Mental health.